2020
DOI: 10.5114/fmpcr.2020.98249
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of stress level and prevalence of depression among haemodialyzed patients

Abstract: Background. chronic kidney Disease is a progressive illness that requires long-term treatment. Frequent hospitalisation due to dialysis is a result of multiple stressors which contributes to depressive disorders. Objectives. the aim of this study was to assess the increase of stress and occurrence of depressive disorders among patients haemodialyzed regarding sociometric and medical data. Material and methods. the study was carried out in a group of 102 patients with chronic kidney Disease who were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Other studies (AlDukhayel, 2015; Bossola et al, 2010; Turkistani et al, 2014) showed that older HD patients were more likely to have higher levels of depression. Consistent with our findings, some previous studies found that sex was not associated with depression levels (AlDukhayel, 2015; Hamody et al, 2013; Starczewska et al, 2020; Turkistani et al, 2014). However, Saeed et al (2012) reported that being female was linked with an increased risk of depression, considering that males are traditionally dominant in the structure of the Arab family.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies (AlDukhayel, 2015; Bossola et al, 2010; Turkistani et al, 2014) showed that older HD patients were more likely to have higher levels of depression. Consistent with our findings, some previous studies found that sex was not associated with depression levels (AlDukhayel, 2015; Hamody et al, 2013; Starczewska et al, 2020; Turkistani et al, 2014). However, Saeed et al (2012) reported that being female was linked with an increased risk of depression, considering that males are traditionally dominant in the structure of the Arab family.…”
Section: Discussionsupporting
confidence: 93%
“…Research has been consistent in showing that measures of catastrophic thinking are significantly correlated with measures of depression, anxiety, and fear [8]. In a study among haemodialysed patients it has been established that pain and self-sufficiency for daily activities are factors of an increase in the stress experienced [29]. In our study, depression and anxiety scores were found to be significantly higher in female patients than in men, but no significant difference was found between the genders in terms of pain catastrophising.…”
Section: Discussionmentioning
confidence: 94%